Culture and Hofstede (1980) in international business studies: a bibliometric study in top management journals - Ferreira, Manuel Portugal (2021)
How countries differ in their fundamental cultural traits and how these differences impact firms and businesses has been a recurring topic in international business research. Geert Hofstede’s (1980) work on culture and the cultural dimensions has had high impact on research carried out in international business studies and has been used in a wider array of business/management disciplines to delve into a large variety of phenomena. In this study, we conduct a bibliometric analysis of the articles published in eight top ranked business journals that quoted Hofstede’s work, over a period of thirty years. Hofstede’s work is used as a key marker for culture. In a sample of 655 articles, we conducted citation and co-citation analyses to better understand the ties binding scholars, theories and ideas. Moreover, a longitudinal analysis of both cocitation and research topics allow us to observe and better understand how much does Hofstede – and culture – matter in international business studies and how research emphasis has changed over time. For instance, we noted how the emphasis of research has shifted from methodological concerns to help explaining, contextualizing why firms made the choices they did, and how operations ought to be managed. We discuss broadly the results, pointing some implications, especially for theory and scholars.